EVALUATION OF CREDITWORTHINESS THROUGH THE CREDIT SCORE MODEL BY SYNERGIC USE OF FINANCIAL AND QUALITATIVE INDICATORS - Andrea Vareško (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
It is well known that in the Croatian economy very little attention is paid to business analysis and business risk management. Also, incompetence and inadequate expertise of top management, as well as superficial and insufficiently professional supervision of business by companies' owners, continuously generate problems with liquidity, over-indebtedness, and losses within Croatian companies. Failure to (timely) address these problems is in essence the cause of a large number of bankruptcies and liquidations of business entities, which ultimately produces serious problems for the Croatian economy in general. In this paper, business analysis and the analysis of business risks of the Uljanik d.d. group. during the period from 2016. to 2017. will be evaluated in order to determine the creditworthiness of the company at that time, respectively before the announcement of the company's bankruptcy in 2019. This paper will try to determine whether the difficulties in business could be promptly identified and whether the company's management structure in the mentioned period could react faster and more decisively based on the assessment of the company's creditworthiness and the knowledge gained during the analysis. The optimal choice of financial and qualitative indicators was used in the evaluation of creditworthiness by which it is possible to make a more reliable assessment of creditworthiness taking into account internal and external factors that affect the company's operations. In the used credit score model, the final credit rating is determined by synthesis and common use of financial and qualitative indicators and provides comprehensive and credible information about the business entity and its business risks and in that way allows the correct business decisions to be taken on time.